Тачки-3: Лучший гонщик (Мои любимые сказки, 2017)
На обл: С персонажами нового фильма! Экземпляры: Ф-9 (20211117) / Инвентарный номер: 96932 / Цена: / Сис.шифр: 84(7=432.1)-4 / Авт.знак: Т 87 / ББК: 84(7=432.1)-4